English English - Winata, I Made Agus Arya; Jodog, I Made; Adi Sucipta, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
This report discusses the utilization of technological advancements along with the work experience that can be gained while being in the digital industry. Fine art is a human expression that combines emotions, beauty, and visual techniques to create works that inspire and communicate meaning. From traditional art forms such as painting and sculpture to modern evolutions like photography, videography, and digital art, fine art has seen significant developments in the media and technology used. Creating art in the digital era is known for its technicalities or complexities, where one needs to understand and operate the tools or software used before diving into the creative process and freedom in applying artistic elements. This development not only expands artistic boundaries but also embraces changes in social, cultural, and technological progress. Digital art, for example, not only offers new possibilities for creative expression but also provides a broader and more accessible platform for artists to convey their messages to a global audience. Thus, fine art not only becomes a part of everyday life but also serves as a key driver in the development and understanding of contemporary art in today's world. With the utilization of technological advancements and the current digital industry, our ability to adapt and provide alternative paths for artists in pursuing their careers has significantly increased.